2006
DOI: 10.1167/iovs.06-0209
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of Diadenosine Polyphosphates in Corneal Epithelial Cell Migration

Abstract: Based on the pharmacological profile of all the compounds tested, the two main P2Y receptors that exist in these corneal cells are a P2Y(2) receptor accelerating the rate of healing and a P2Y6 receptor that delays this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Experiments performed in our laboratory on an animal model, demonstrated that the levels of Ap 4 A and Ap 5 A are significantly reduced after the damage, recovering after 10 h. The same ratio of Ap 4 A/Ap 5 A concentration in tears remained stable. This means that diadenosine polyphosphates remain low during the latency phase and recover during the migration phase, suggesting their involvement in the migration process (Mediero et al, 2006).…”
Section: Effect On Corneal Wound Healingmentioning
confidence: 93%
See 4 more Smart Citations
“…Experiments performed in our laboratory on an animal model, demonstrated that the levels of Ap 4 A and Ap 5 A are significantly reduced after the damage, recovering after 10 h. The same ratio of Ap 4 A/Ap 5 A concentration in tears remained stable. This means that diadenosine polyphosphates remain low during the latency phase and recover during the migration phase, suggesting their involvement in the migration process (Mediero et al, 2006).…”
Section: Effect On Corneal Wound Healingmentioning
confidence: 93%
“…The expression of P2 receptors in different ocular surface locations suggests the involvement of these receptors in the physiology of the eye (Guzman-Aranguez and . In fact, during the last decade, the role of several nucleotides and their receptors in ocular processes, including tear secretion (through P2Y 2 receptor) (Jumblatt and Jumblatt, 1998;Murakami et al, 2000), corneal wound healing (P2Y 2 is able to accelerate the corneal re-epithelization and proliferation, meanwhile P2Y 6 inhibits the process) (Byun et al, 2016;Crooke et al, 2009;Mediero et al, 2006), and corneal epithelial migration and stromal organization (mediated through P2X7 receptor) have been described (Mankus et al, 2012;Mayo et al, 2008).…”
Section: Ocular Surfacementioning
confidence: 99%
See 3 more Smart Citations